2000
DOI: 10.1177/172460080001500207
|View full text |Cite
|
Sign up to set email alerts
|

Pepsinogen C Expression in Tumors of Extragastric Origin

Abstract: We have examined by immunohistochemistry the ability of human carcinomas of various origin to produce pepsinogen C, an aspartyl proteinase mainly involved in the digestion of proteins in the stomach and recently found to be associated with breast carcinomas. Of the 268 tumors analyzed 80 (29.8%) showed positive staining for pepsinogen C. These positive tumors included 12 gastric (38.7% of the 31 examined cases), nine pancreatic (42.8%), two renal (20%), 12 prostatic (40%), three bladder (27.3%), 14 endometrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…PGC is synthesized in the gastric mucosa and secreted into the gastric lumen, where it is converted into the active enzyme pepsin C under acidic conditions (5,6). Surprisingly, previous studies have reported ectopic expression of PGC in several carcinomas of extragastric origin.…”
Section: Introductionmentioning
confidence: 99%
“…PGC is synthesized in the gastric mucosa and secreted into the gastric lumen, where it is converted into the active enzyme pepsin C under acidic conditions (5,6). Surprisingly, previous studies have reported ectopic expression of PGC in several carcinomas of extragastric origin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition PGC activity has been reported in tumours of extra-gastric origin including breast, bladder and prostate [14]. The significance of PGC in these tumours is not known but PGC expression appears to be hormonally regulated [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…34,35 As such, pepsin in the lower airways may simply refl ect proximal refl ux (laryngopharyngeal refl ux). A second important consideration is that, unlike pepsinogen A, pepsinogen C has been identifi ed in extragastric 36 sites, including the lungs. [37][38][39] Specifi cally, it appears to be expressed by type 2 pneumocytes and is involved in surfactant B processing.…”
Section: Resultsmentioning
confidence: 99%